Investigating child sexual violence among secondary school learners in Wakiso District, Uganda - Israel Kibirige; Tumusiime Margaret (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Child Sexual Violence (CSV) is a global challenge, and its prevalence is not well studied in Ugandan schools. This study used a cross-sectional design to investigate CSV prevalence and its relationship with parental care and learners' characteristics among secondary school learners in the Wakiso District. The sample comprised 274 learners from five schools: rural, peri-urban, and urban. A 4-Likert questionnaire comprising parental care, learners' characteristics, and CSV was used to collect data. Data were analysed using means, standard deviation, Chi-square, and Analysis of Variance–ANOVA. The results show high CSV prevalence among learners with low parental care and low personal characteristics, where sexual harassment, defilement, and rape accounted for 60.10%, 55.11%, and 51.10%, respectively. There were no significant differences in CSV prevalence among rural, peri-urban and urban schools (ANOVA, p = .25). Implications for schools to minimise CSV in schools are discussed